Statement on the March Moscow meeting, adopted by the political committee of the communist party of New Zealand (March 24, 1965. (Peking : Foreign Languages Press, 1965)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: communistische partijen; Nieuw-Zeeland.